2022
DOI: 10.3390/healthcare10112208
|View full text |Cite
|
Sign up to set email alerts
|

Primary Healthcare Nurse’s Barriers and Facilitators to Providing Sexual and Reproductive Healthcare Services of LGBTQI Individuals: A Qualitative Study

Abstract: In most cases, we only hear Lesbians, Gays, Bisexuals, Transgender, Queer, and Intersex (LGBTQI) patients complaining about nurses being the reason for not accessing and utilizing healthcare services; for example, studies reports on the different attitudes of healthcare providers including nurses against LGBTQI patients. However, factors influencing the behavior of South African Primary Healthcare (PHC) Nurses toward LGBTQI patients are rarely reported. The study aimed to explore how PHC nurses experienced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Empathy from HCPs, while typically positive, may impede effective communication and service delivery to queer people, highlighting a need for increased education and cultural competence within healthcare institutions. Synthesizing the results from multiple studies, we can conclude that one of the most signi cant barriers to queer utilization and accessibility of healthcare services is a lack of education, understanding, and competence among HCPs regarding queer people's related health issues [10,13,34]. Our ndings are consistent with several studies that found an absence of awareness among HCPs about transgender-related health issues [20], a de ciency of HCP awareness and insensitivity to the unique needs of this community [21], and a lack of understanding of transgenderspeci c well-being issues by HCPs [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy from HCPs, while typically positive, may impede effective communication and service delivery to queer people, highlighting a need for increased education and cultural competence within healthcare institutions. Synthesizing the results from multiple studies, we can conclude that one of the most signi cant barriers to queer utilization and accessibility of healthcare services is a lack of education, understanding, and competence among HCPs regarding queer people's related health issues [10,13,34]. Our ndings are consistent with several studies that found an absence of awareness among HCPs about transgender-related health issues [20], a de ciency of HCP awareness and insensitivity to the unique needs of this community [21], and a lack of understanding of transgenderspeci c well-being issues by HCPs [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these SDGs, notably SDG 3.7, seek to provide universal access to sexual and reproductive healthcare services by 2030 [7]. Speci cally, in SA, queer people continue to face di cult and diverse social challenges such as prejudice, stigmatization, denial of healthcare services, and community rejection [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%